The genomic epidemiology of typhoidal and invasive nontyphoidal Salmonella in sub-Saharan Africa - Park, E (2019)
Invasive salmonellosis is one of the most common community-acquired bloodstream infections among children and immunocompromised adults in sub-Saharan Africa. Clean water, improved sanitation and hygiene, which are essential for disease prevention and control, remain limited in most resource constrained countries. Typhoid fever and invasive nontyphoidal Salmonella (iNTS) disease have historically been managed by antimicrobial therapy. Ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole (co-trimoxazole) served as the first choice of drugs for many years, but antimicrobial resistance (AMR)/multi-drug resistance (MDR) in these pathogens have emerged and spread inter-/intra-continentally. In this thesis, I conducted genomic, phylogenetic, and epidemiological analyses of invasive salmonellosis in Africa. My analysis supported existing hypotheses regarding the association between iNTS disease and plasmodium falciparum malaria in sub-Saharan Africa. Regarding the MDR typhoid fever, I found geographically distinct MDR S. Typhi lineages circulating in West (genotype 3.1.1) and East (genotype 4.3.1) Africa with high MDR incidence rates (>100/100,000 person-years observation) among children under 15 years old, particularly in Burkina Faso, Ghana and Kenya. iNTS disease was predominantly caused by S. Typhimurium ST313 and S. Enteritidis ST11, which circulate across the African continent and were largely MDR. High MDR incidences (>100/100,000 PYO) of iNTS disease was found in children less than five years old across multiple countries; namely Burkina Faso, Ghana, and Guinea Bissau. Reduced susceptibility to fluoroquinolones was found in both S. Typhi (genotype 4.3.1 in East Africa; Kenya/Uganda) and iNTS (S. Enteritidis ST11 and S. Typhimurium ST313 in West Africa; Ghana). Third generation cephalosporin resistant S. Typhimurium ST313 was found in Kenya; a novel resistance-virulence IncI1 plasmid associated with S. Enteritidis ST11 isolates was also identified in Ghana, Senegal and Burkina Faso. Further, I conducted genomic analyses of NTS organisms isolated from stool samples of individuals living in selected communities in sub-Saharan Africa (Guinea-Bissau/Senegal). These data revealed a highly diverse collection of NTS serovars/sequence types, evidence of household transmission events, and found an S. Enteritidis ST11 isolate carrying IncF virulence plasmid in Senegal. These studies demonstrate the importance of continued disease surveillance combined with genomics to better understand the epidemiological landscape of invasive salmonellosis in Africa.